International relations in a relational Universe - Kurki, Milja; Oxford Scholarship Online (Online service). (New York Oxford University Press, 2020)
Building a conversation between relational cosmology, developed in natural sciences, and critical social theory, this book seeks to develop a new perspective on how to think relationally in and around the study of IR
Includes bibliographical references (pages 201-212) and index
Keywords: Electronic books; International relations -- Philosophy; Relationism